Discovery of novel dual-targeting inhibitors against PLK1-PBD and PLK4-PB3: structure-guided pharmacophore modelling, virtual screening, molecular docking, molecular dynamics simulation, and biological evaluation - Changhao Zhao; Hanying Wu; Huajing Liu; Hui Dong; Miao-Miao Niu; Kun Shi; Fengzhen Wang (Journal of Enzyme Inhibition and Medicinal Chemistry, 2025)
Aberrant expression of PLK1 and PLK4 is closely associated with tumourigenesis, and their simultaneous inhibition can effectively suppress tumour proliferation. In this study, we successfully identified peptide inhibitors (Peptides 1–5) capable of simultaneously targeting PLK1-PBD and PLK4-PB3 via pharmacophore-based virtual screening. Binding affinity analyses demonstrated that all candidate peptides exhibited nanomolar binding affinity for both targets. In vitro cancer cell growth inhibition assays revealed that these peptides could suppress the growth of cervical cancer cells. Among them, Peptide-2 showed the optimal binding affinity and anticancer cell proliferative activity (PLK1-PBD: Kd = 8.02 ± 0.16 nM; PLK4-PB3: Kd = 11.32 ± 0.19 nM; IC50 = 0.44 ± 0.03). Molecular dynamics (MD) simulations further predicted that Peptide-2 could stably bind to the binding sites of both PLK1-PBD and PLK4-PB3. This study reported a novel peptide inhibitor Peptide-2 with potent dual-target inhibitory activity against PLK1-PBD/PLK4-PB3, providing a novel strategy for cancer therapy.